Sistemas de transposição de peixes: um facilitador da migração ou introdução de espécies? - Topan, Dhyego Amilton (2018)
Migratory species are the most affected by construction of dams because they have their migratory routes interrupted, and so, management measures were created to mitigate these impacts, such as the fish transposition systems (FTSs). Howhever, these systems have questionable efficiency and can also facilitate the introduction of species. Thus, we test the hypothesis that there is a positive relationship between the density of migratory fish larvae and the construction of the Canal da Piracema in the Itaipu dam, and if the main species that are using the channel are native or non-native to the Parque Nacional de Ilha Grande (PNIG). We collected fish larvae during 12 reproductive windows (October to March) between 2001 and 2016, we calculated the total mean density, and the densities before and after the opening of the Canal da Piracema. We used the principal component of neighboring matrices, followed by partial canonical redundancy analysis (PCNM-RDAp) to evaluate the temporal influence of the channel and the environmental variables under the abundance of fish larvae. It was possible to observe the presence of larvae of migratory species in the PNIG, but contrary to our expectations, the density of migratory larvae decreased after the canal opening. However, the decrease occurred due to the impact on the native species, because the non-native ones were favored, Pterodoras granulosus for example, had a considerable increase after the channel opening, and was among the most abundant in the PNIG. In this way, the channel, instead of acting as a management and conservation measure to native migratory species, it facilitated the introduction of species, since it connected two ichthyofaunistic provinces previously separated by the Itaipu dam.